Toward a level playing field: The roles of mentors and critical friendships in the lives of women doctoral students - Catherine Hansman-Ferguson; Patricia Garofolo (Adult Education Research Conference, 1995)
This study examines mentoring relationships and supportive friendships formed by women doctoral students in an adult education program and examines how these affinities affected the women students’ persistence in pursuing their doctoral degrees.